Ground reflection model in rough surface forUWB impulse radio - Vongsripeng, Porntape; Promwong, Sathaporn; Supanakoon, Pichaya; Chamchoy, Monchai; Keawmechai, Sompoph (My University, 2005)
Ultra-wideband (UWB) is currently wide interesting technology of wireless communication technology in building and home entertainment. In order to be the most effective wireless communications, we have to consider the parameters which are vital signal transmission factors of UWB. As a consequent, imitation of UWB signal transmission in two-part model so as to notice reflected signal from several rough types of ground such as Brick and Limestone is demonstrated in this abstracts. Friis' transmission formula and Rayleigh equation are used to calculate in this model for searching any effects happened by reflection of rough ground and analyzed in path loss, path gain and time dispersion as RMS delay spread. © 2005 IEEE.
Keywords: Reflection; Scattering; Two-path model and Ground Reflection Model; Ultra-wideband